INFLUENCE OF BONE MARROW MSCs ON THE DEVELOPMENT OF POSTTRANSPLANT CHANGES IN KIDNES - N. A. Onishchenko; S. S. Meshcherin; I. M. Ilyinsky; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2016)
Aim: to study of infl uence of various doses of autologous BM MSCs on the development of chronic transplant nephropathy in a decentralized kidney using kidney autotransplantation model (KAT).Materials and methods. Five groups of experiments were performed on 105 Wistar rats. The model of kidney autotransplantation by means of surgical decentralization (denervation – delymphatization) and infl ammation induction with kidney antigen and Freund’s adjuvant was created in groups I, II and III. Group I served as a decentralization control (control 1). In groups II and III autologous BM MSCs were injected intravenously once 35–40 days after surgery – a high dose in group II: 3.0–5.0×106 cells; a low dose in group III: 0.3–0.5×106 cells; group IV served as intact control; group V served as intact control with the injection of the same dose of BM MSCs as in group II. Kidney excretory functions (diuresis, creatinine, urea, protein in blood and urine, sodium excretion) and morphology were examined during months 3, 5 and 7–10.Results. In all five groups over the study duration nitrogen excretion was not disrupted. High doses of BM MSCs after KAT modeling resulted after month 3 in pronounced proteinuria in all rats (3–3.5 times more than in group I) and gradually decreased diuresis; histologically severe focal cell infiltration and the accumulation of protein masses in lumina of glomeruli and tubules were observed. By month 10 glomerular and tubulointerstitial focal sclerosis was developed. Low doses of BM MSCs after KAT modeling led to gradual decrease of proteinuria after month 3 reaching the initial values by months 5 and 7 of observation; histologically rare foci of cellular infiltration around glomeruli were observed.Conclusion. A single application of low doses of BM MSCs is capable of protective desensitizing infl uence on the tissue of decentralized kidney and can prolong the duration of kidney function without signs of pronounced damage, while under the same conditions high doses of autologous BM MSCs lead to accelerated development of severe chronic transplant nephropathy.